Coping With Pain Severity, Distress, and Consequences in Women With Ovarian Cancer. - Gilbertson-White, Stephanie; Campbell, Grace; Ward, Sandra; Sherwood, Paula; Donovan, Heidi (Cancer Nursing)
Background: Self-regulation can be useful in understanding pain management efforts in women with ovarian cancer. Self-regulation is a parallel process of problem- and emotion-focused coping; problem-focused coping involves efforts aimed at solving/reducing the problem directly, whereas emotion-focused coping is aimed at managing negative emotions. Objectives: The aims of this study were to describe the types of problem- and emotion-focused coping strategies used to manage pain severity, distress, and consequences and to evaluate whether there was evidence of parallel processing (ie, use of a combination of both problem- and emotion-focused strategies). Methods: Women (n = 162) from a cross-sectional study of cancer symptoms who reported pain as a most noticed symptom in the past week were included. Pearson correlations and t tests were used to evaluate relationships among the variables. Results: Mean pain severity was 5.5 (SD, 2.7) on a 0- to 10-point scale. An average of 4.6 (SD, 2.1) coping strategies were reported. Actively manage and planning were the most frequent problem-focused strategies; relaxation was the most frequent emotion-focused strategy. Higher total number of coping strategies attempted, expressing emotions, and seeking emotional support were associated with higher pain distress and consequences scores, and actively managing pain was associated with higher pain severity. Conclusion: Women with a history of ovarian cancer continue to experience severe pain. Partial support for parallel processing was found.